Successful selective reduction of a heterotopic cesarean scar pregnancy in the second trimester: a case report and review of the literature. Issue 1 (December 2016) - Yu, Haiyan; Luo, Hong; Zhao, Fumin; Liu, Xinghui; Wang, Xiaodong
Abstract Background Heterotopic cesarean scar pregnancy is a cesarean scar pregnancy combined with an intrauterine pregnancy that predisposes a woman to life-threatening complications such as uterine rupture and massive bleeding. Preservation of the intrauterine pregnancy in heterotopic cesarean scar pregnancy is a great challenge. Case presentation We report a case of a 33-year-old woman with heterotopic cesarean scar pregnancy after IVF-embryo transfer (ET). Expectant management was carried out with early diagnosis of heterotopic cesarean scar pregnancy (HCSP), and selective fetal reduction of cesarean scar pregnancy (CSP) was performed by ultrasound-guided intrathoracic injection of potassium chloride (KCl) at 16 + 4 weeks of gestation due to aggravation of CSP. Preservation of the intrauterine pregnancy was successful and a healthy baby was delivered by cesarean section at 37 + 6 weeks of gestation. Conclusions Heterotopic cesarean scar pregnancy is an extremely rare form of heterotopic pregnancy. Patients should be appropriately counseled regarding the different treatment options available. An ultrasound-guided injection of potassium chloride may constitute a safe, minimally invasive and reliable way to terminate the heterotopic gestation and preserve the intrauterine pregnancy. Intensive management should be performed during the ongoing pregnancy and cesarean section.